The Influence Of Instructional Leadership Of Middle Managers On Teacher Commitment Through Professional Learning Community And The Role Of Trust In Leader As A Moderator - Amin, Nor Aiza Zamzam (2018)
This study investigates the influence of instructional leadership of middle managers on teacher commitment, professional learning community (PLC) as the mediator and trust in leader as the moderator on the relationship between instructional leadership and teacher commitment. This study is designed using the survey method. The questionnaire was adapted from Principal Instructional Management Rating Scale (PIMRS) by Hallinger and Murphy (1985), Professional Learning Community Assessment (PLCA) by Huffman and Hipp (2003), Omnibus T-Scale by Hoy and Tschannen-Moran (2003) and teacher commitment by Nordin (2007). The questionnaire was administered to 400 secondary school teachers based on their geographical locations which have been clustered into zones using a multi-stage sampling.